MON-061 A Case of Central Precocious Puberty Patient with Arnold Chiari Malformation, Type I - Kim, Dae Hyun (J Endocr Soc, 2020)
Central precocious puberty (CPP) is caused by early activation of Hypothalamo-Hypophyseal-Gonal (H-P-G) axis. Although the cause of CPP is idiopathic in most cases, small portions of CPP are caused by intracranial lesion such as hypothalamic hamartomas, postencephalitic scars, tubercular meningitis, head trauma, hydrocephalus, tuberous sclerosis, arachnoid cyst, etc. Type I Chiari malformation is a disorder characterized by a displacement of the cerebellar tonsils through the foramen magnum into the upper cervical spinal canal with various neurologic symptom. There have been some reported cases of Arnold-Chiari type I malformations with CPP, however this association is not yet completely understood. We would like to introduce a case of girl experiencing Arnold Chiari type I malformation as well as CPP, who presented with progressive breast budding and acceleration of growth. A 8-year-old girl was presented with 6month history of breast budding and acceleration of growth (5cm/7month). Her family history demonstrated that her mother had been treated with prolactinoma and experienced early menarche. On physical examination, she showed Tanner stage 2(B2, P1). She did not exhibit any neurological signs or symptoms. Thyroid gland was not enlarged and No abnormal skin pigmentation or bony abnormalities were identified. Her height was 124.9cm (37th percentile), weight was 22.4kg (14th percentile), while midparental height was calculated to be 159cm (father: 174cm, mother: 157cm). Her bone age was assessed to be 10 years of age. Luteinizing hormone(LH) showed pubertal response (peak LH: 9.9IU/L) in Luteinizing Hormone Releasing Hormone (LHRH) stimulation test. The abdominopelvic US revealed pubertal response of uterus(length 4.1cm, endometrial echogenicity) without any other abnormality. We performed brain Magnetic Resonance Imaging(MRI) for rule out intracranial lesion, which showed Arnold-Chiari type 1 malformation (downward displacement of the cerebellar tonsil by 6 mm). Following diagnosis, Her parents wanted further neurologic evaluation and treatment in Canada, beacause she was Canadian. In conclusion, Arnold-Chiari type 1 malformation can be a possible cause of CPP without neurological symptoms in children, more cases are needed to clarify the relationship and evaluate reasonable causes of Arnold-Chiari type 1 malformation in the brain, especially in young patients with precocious puberty.